2018
DOI: 10.1039/c8cc05595e
|View full text |Cite
|
Sign up to set email alerts
|

Structure-inspired design of a sphingolipid mimic sphingosine-1-phosphate receptor agonist from a naturally occurring sphingomyelin synthase inhibitor

Abstract: A monophosphate derivative of ginkgolic acid binds to sphingosine 1-phosphate (S1P) receptors to perform similar functions to the lipid mediator S1P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…These effects could be explained by the modulation of S1Pdependent signals through formation of S1P receptor heterodimers (Van Brocklyn et al, 2002;Zaslavsky et al, 2006;Siehler and Manning, 2002;Kluk and Hla, 2002), which has been previously described in other cells and also for other receptors expressed in granulosa cells (Casarini et al, 2018a). However, we can not exclude that synthetic ligands and S1P may activate different conformational states of the receptors, and hence a distinct profile of intracellular signaling cascades (Troupiotis-Tsaïlaki et al, 2017;Swamy et al, 2018;Jiang and Zhang, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…These effects could be explained by the modulation of S1Pdependent signals through formation of S1P receptor heterodimers (Van Brocklyn et al, 2002;Zaslavsky et al, 2006;Siehler and Manning, 2002;Kluk and Hla, 2002), which has been previously described in other cells and also for other receptors expressed in granulosa cells (Casarini et al, 2018a). However, we can not exclude that synthetic ligands and S1P may activate different conformational states of the receptors, and hence a distinct profile of intracellular signaling cascades (Troupiotis-Tsaïlaki et al, 2017;Swamy et al, 2018;Jiang and Zhang, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…The ability of DCA and its derivatives to inhibit the SMS isozymes SMS1 and SMS2 was evaluated using a cell lysate assay and the fluorescent substrate C6-NBD (4-nitrobenzo-2-oxa-1,3-diazole)-Cer. DCA ( 1 ) and compounds 4 , 6 , and 7 showed relatively moderate inhibitory activities, with IC 50 values of 7, 17, 9, and 4 μM, respectively, for SMS1, and 4, 10, 7, and 5 μM, respectively, for SMS2 ( Figure 1 ), similar to other natural compounds [ 13 , 14 ]. These findings indicated that the methyl esters of DCA derivatives, compounds 2 , 3 , and 5 , were inactive in these assays.…”
Section: Resultsmentioning
confidence: 57%
“…However, the SMS has not been succeeded in its crystallization. Therefore, a direct comparison with the previously isolated SMS inhibitor ginkgolic acid [ 13 ] has been examined. The chemical similarity of ginkogolic acid to DCA, as it is a long alkyl chain and a carboxylic acid moiety in an aromatic ring, shows that these two inhibitors also have the same functional group participation to inhibit SMS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assay uses a fluorescent (D)‐ erythro C6‐NBD (4‐nitrobenzo‐2‐oxa‐1,3‐diazole)‐Cer analog as a substrate into SM moiety. As shown in Table , several ceramides showed relatively moderate inhibitory activities (IC 50 0.2‐1 μM; Table ) compared with those of our previously reported natural compounds . Furthermore, to determine the differences in the inhibitory activities of the four stereoisomers, we represented the IC 50 values as a heatmap graphical representation in which individual values contained in a matrix are displayed as colors.…”
Section: Resultsmentioning
confidence: 99%